Pheochromocytoma An Unusual Presentation A Case Report (Journal of Bangladesh College of Physicians and Surgeons, 2010)
This case report is of a 50yrs old man who got admitted inBIRDEM Hospital in a state of unconsciousness for 5 hours.He is a known case of hypertension and diabetes mellitusfor the last 12 years and was on insulin. Hypoglycemia wasdetected, treated with intravenous glucose and the patientregained consciousness. On further query he complainedof repeated episodes of nausea, palpitation and sweatingfor the last 12 years. The episodes were initially labeled ashypoglycemia but blood sugar was never found inhypoglycemic range. The patient was on multipleantihypertensive medications but blood pressure wasuncontrolled. All the investigations were normal including24hrs urinary VMA, serum adrenalin and noradrenalinexcept ultrasonography of whole abdomen which showed amass measuring 72x 76 mm in left suprarenal region. Onenight the patient again developed palpitation, chestdiscomfort, severe headache and profuse sweating. Bloodpressure was recorded 240/160 mmHg. Blood sample wasdrawn for adrenalin, noradrenalin, 24hrs urine collectionwas done for VMA and was found very high. The patientwas diagnosed as having left adrenal pheochromocytoma.After controlling blood pressure and other preoperativepreparations left adrenalectomy was done. Histopathologyrevealed phaeochromocytoma. Per and postoperativeperiods were quite eventful. Blood pressure was normalwithout any antihypertensive drug during discharge. Thepatient was discharged with the advice to come for followup after 1 month.DOI: 10.3329/jbcps.v28i2.5371J Bangladesh Coll Phys Surg 2010; 28: 113-116